The Opinion of Hacettepe University Department of Information Management About Classifying The Education At Information Management Departments as “Vocational Technical Higher Education” - Hacettepe Üniversitesi BBY Bölümü (Türk Kütüphaneciliği)
Technical services category reasons of librarians in Turkey are shared by Hacettepe University Department of Information Management in the professional discussion list kutup-l as an academic comment for some barriers recently.